Analisis Kepribadian Pada Tokoh Caraka Dalam Novel Let Go Karya Windhy Puspitadewi : Kajian Psikologi Sigmun Freud - Aryo Nur Hidayat; Albertus Risto Sava Tadeo; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to describe the personality of the character Caraka in the novel Let Go by Windhy Puspitadewi. This type of research is qualitative research. The data collection method used in this research is the descriptive method. The data analysis method used is Sigmund Freud's theory of personality on aspects of personality structure which consist of Id, Ego and Super Ego. The results of the analysis in the novel Let Go by Windhy Puspitadewi show a strong Id Caraka who can be described as someone who likes to interfere in other people's problems which should not be his responsibility. The ego aspect of Caraka's character is described as someone who really loves his friend (Nathan) because he has made himself better. The superego aspect of Caraka's character is depicted when he convinces Nathan to stay alive.